Total Quality Management And Supply Chain Management On Operational Performance - Umi Nur Qulub; Dessy Isfianadewi (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study aimed to determine the effect of total quality management (TQM) and supply chain management (SCM) practices on operational performance in MSME gift shops in Sleman, Yogyakarta. The method used in this study was a quantitive approach by distributing questionnaires directly to gift shops one by one. There were 135 respondents with gift shop owners, managers, and supervisors backgrounds. The measurement scale used is a 5 Likert scale, where the respondent's answer has a score weight: 1 = strongly disagree, 2 = disagree, 3 = neutral, 4 = agree, and 5 = strongly agree. This study data analysis uses the SEM method using PLS, tested using the Smart PLS 3.2.9 tool. This study found that implementing TQM and SCM significantly influenced operational performance. This study also found that good TQM practices in souvenir shops include top management support, customer focus, and employee involvement. The findings of this study were as follows: 1) TQM has a positive effect on SCM, 2) SCM has a positive effect on operational performance, and 3) TQM has a positive effect on operational performance.